2010
DOI: 10.1002/pds.1946
|View full text |Cite
|
Sign up to set email alerts
|

Persistence with cholinesterase inhibitor therapy in a population‐based cohort of patients with Alzheimer's disease

Abstract: The likelihood of discontinuing ChEI therapy was high in this real-world sample of AD patients. Significant predictors included clinical, socioeconomic, and practice factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
64
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 49 publications
(120 reference statements)
9
64
0
1
Order By: Relevance
“…Stopping treatment may have occurred because of the apparent lack of effectiveness. Interestingly, the lower risk for ChEI discontinuation observed for older patients with AD in the study by Amuah et al 44 was only apparent in analyses restricted to those who remained eligible for coverage (that is, did not show evidence of decline in both their cognitive and functional abilities).…”
Section: Patient-level Factorsmentioning
confidence: 95%
See 4 more Smart Citations
“…Stopping treatment may have occurred because of the apparent lack of effectiveness. Interestingly, the lower risk for ChEI discontinuation observed for older patients with AD in the study by Amuah et al 44 was only apparent in analyses restricted to those who remained eligible for coverage (that is, did not show evidence of decline in both their cognitive and functional abilities).…”
Section: Patient-level Factorsmentioning
confidence: 95%
“…While many studies reported no statistically significant association between ChEI persistence and age or sex, several reports suggest that older patients (for example, aged 75 and older) 34,38,39,45,46,50,53 and female patients 34,43,44 may be more likely to discontinue ChEI therapy. An association with advanced age may reflect the impact of more advanced disease severity, 31 a perceived lack of therapeutic benefit, or concerns about a heightened risk for adverse effects.…”
Section: Patient-level Factorsmentioning
confidence: 99%
See 3 more Smart Citations